Templated growth formation of mesoporous silica materials: a soft-hard template approach - Reva Edra Nugraha; Nur Aini Fauziyah; Guardiola Rosa Wira (Future Science, 2022)
Mesoporous silica is continuously raising in popularity due to its excellent and unique properties, such as customizable pore, surface shape/morphology, large pore volume, and ease of functionalization for wide applications like catalysis, energy, environment, and biomedical areas. In the templated growth synthesis, a template acts as a mesostructure-directing agent to produce hollow porous structures in silica frameworks. Templates can be divided into